Pengaruh Media Video Animasi terhadap Perilaku Hidup Bersih dan Sehat Mencuci Tangan 6 Langkah pada Siswa Sekolah Dasar - Emilyani, Desty; Kurnia, Theresia Avila; Mawaddah, Ely; Rusmini, Rusmini; Andini, Saskiyanti Ari; Riamah, Riamah (Poltekkes Kemenkes Mataram, 2024)
Several diseases suffered by children are caused by the transmission of bacteria through the hands due to not washing hands with soap properly and correctly, such as ISPA, Covid 19, diarrhea and worms. Data on the proportion of hand washing behavior in NTB Province is 46.47%, while data in West Lombok is 49.54%. This research aims to analyze the influence of the 6-step hand washing animation video media on clean and healthy living behavior among students at elementary school. The design of this research is a one group pre test - post test design with two variables, namely the independent variable: animated video media and the dependent variable: clean and healthy living behavior, washing hands in 6 steps. With a total sample of 39 respondents. The research results show that there is an influence of the six-step hand washing animation video media on clean and healthy living behavior as proven by the Wilcoxson statistical test with a p-value of 0.000. In the areas of knowledge, attitudes and skills. Animated video media makes it easier for children to understand information so that they can improve their knowledge, attitudes and skills. Animated video media can stimulate children's thoughts, feelings and motivation through moving picture illustrations accompanied by narrative sound and serves to clarify the meaning of the message conveyed.